MEGEMBANGKAN KECERDASAN KINESTETIK ANAK USIA DINI MELALUI SENAM IRAMA ALAT PITA - Melati Susianti Marbun; Indri Mutia Rachmadini; Sherli Nurhavivah; Sri Indriani Harianja (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Early childhood Early childhood is a golden period for children's development to obtain an educational process. One way to optimize children's development is to teach them about physical motor development. Kinesthetic intelligence is an intelligence where when we use it we are able to make beautiful and meaningful movements. The aim of this research is to determine the role of kinesthetic intelligence in early childhood through rhythmic gymnastics using ribbon equipment. The method used in this research is the intuitive and deductive method. Intuitive data was obtained by carrying out rhythmic exercise activities carried out by the author himself. Deductive data is carried out by examining reliable theories and opinions such as books, journals, laws and the like. The results of implementing rhythmic gymnastics with ribbon equipment can develop kinesthetic intelligence in early childhood. Using additional media such as ribbons can make children more enthusiastic about doing gymnastics.